Certified reference materials for analytical quality control in neutron activation analysis - Wee, Boon Siong; Abdul Khalik, Wood; Mohd. Suhaimi, Hamzah; Shamsiah, Abdul Rahman; Md. Suhaimi, Elias; Nazaratul Ashifa, Abdullah Salim (International Atomic Energy Agency (IAEA), 2007)
Analytical quality control in neutron activation analysis (NAA) requires the use of certified reference materials (CRM) in order to produce reliable analytical results. It is essential to evaluate the performance of NAA method when analyzing various sample matrices. Therefore, the CRM selected for an analysis should be suitable for the type of samples. There are many aspects such as concentration range, matrix match, sample size, and uncertainty, which need to be considered when selecting a suitable CRM. Eventually, results of analysis of CRM were plotted into control charts in order to evaluate the quality of the data. This is to ensure that the results are within the 95% confidence interval as stipulated in the certificate of CRM. Thus, this article aims to discuss the uses of certified reference materials for quality control purposes in NAA involving various sample matrices.